Factors Affecting The Performance Of South Sumatra Police Brigade Personnel - Satria, Nando Dwi; Susanti, Neri; Rahman, Abdul (Universitas Dehasen Bengkulu, 2024)
The purpose of this research is to determine whether there is an influence of leadership and work motivation on employee performance partially and simultaneously.The data collection methods used are questionnaires and documentation. The data collected was analyzed using multiple linear regression analysis with partial hypothesis testing (t test) and simultaneous test (F test). The results of data regression analysis show the following equation Y = 6.325 + 0.714 X1 + 0.151 X2. These results show that leadership (X1) has an influence of 0.714 and motivation (X2) has an influence of 0.151 on employee performance (Y). Based on the hypothesis test, the t test (partial test) shows that the leadership variable (X1) has a significant positive effect on employee performance where t count is 4.336 > t table 1.701 and the significance level is 0.000 < 0.05, so Ho is rejected or Ha is accepted, so that partially there is an influence significant positive relationship between leadership (X1) and employee performance (Y). The motivation variable (X2) shows that there is no significant influence between motivation (X2) on employee performance (Y) where t count is 0.915 < t table 1.701 and the significance level is 0.386 < 0.05, so Ho is rejected or Ha is accepted, so partially it is not there is a significant influence between motivation (X2) on employee performance (Y).